2018
DOI: 10.1093/mnras/sty898
|View full text |Cite
|
Sign up to set email alerts
|

Interferometric diameters of five evolved intermediate-mass planet-hosting stars measured with PAVO at the CHARA Array

Abstract: Debate over the planet occurrence rates around intermediate-mass stars has hinged on the accurate determination of masses of evolved stars, and has been exacerbated by a paucity of reliable, directly-measured fundamental properties for these stars. We present long-baseline optical interferometry of five evolved intermediate-mass (∼ 1.5 M ⊙ ) planet-hosting stars using the PAVO beam combiner at the CHARA Array, which we combine with bolometric flux measurements and parallaxes to determine their radii and effect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 99 publications
4
34
0
Order By: Relevance
“…Both comparisons show that our temperatures are on average ∼ 100 K hotter, which is comparable to previously found offsets between temperature scales (Pinsonneault et al 2012) and well within the systematic uncertainty of the fundamental interferometric temperature scale itself (e.g. White et al 2018). Based on these comparisons we have adopted a conservative uncertainty of 3% on the temperatures in the ATL, which encompasses both random and systematic uncertainties from the literature comparisons.…”
Section: Comparison To Literature Valuessupporting
confidence: 85%
“…Both comparisons show that our temperatures are on average ∼ 100 K hotter, which is comparable to previously found offsets between temperature scales (Pinsonneault et al 2012) and well within the systematic uncertainty of the fundamental interferometric temperature scale itself (e.g. White et al 2018). Based on these comparisons we have adopted a conservative uncertainty of 3% on the temperatures in the ATL, which encompasses both random and systematic uncertainties from the literature comparisons.…”
Section: Comparison To Literature Valuessupporting
confidence: 85%
“…The diameter measurements in both papers are based on only two observations, so they could be more susceptible to systematic errors. Also, Casagrande et al (2014) and White et al (2018) found increased discrepancies as the angular diameters approached the resolution limits, which is the case here with such a value for the angular diameter for HD 3360. We also compared our extinction values with those of Challouf et al (2014).…”
Section: Comparison With the Literaturesupporting
confidence: 75%
“…We then placed Gaussian priors on T eff , Fe H [ ], and R å for the full EXOFASTv2 analysis using the values listed above. The error limits for stellar effective temperature and thus radius are set by the accuracy of interferometric angular diameters, which show systematic differences in excess of 3% (e.g., White et al 2018). We therefore adopted fractional errors of 1.5% for T eff and 3.5% for stellar radius, yielding priors of…”
Section: Global Analysismentioning
confidence: 99%